Sosiologi Praktik Magang Siswa SMK Islam: Studi tentang Habitus Kerja, Etika Profesi dan Internalisasi Nilai Keagamaan - Rifki Nur Aziz; M. Hanif (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study discusses the internship practices of Islamic vocational high school students as a space for the formation of work habitus, professional ethics, and the internalization of religious values. The research problem arises from industrial demands emphasizing punctuality, compliance with standard operating procedures (SOPs), workplace communication, occupational safety, and responsibility, while Islamic schools simultaneously equip students with adab (proper conduct), discipline, and religious values. The purpose of this study is to explain the empirical practices of internships, the social relations supporting the learning process in industry, and the implications of religious education for Islamic vocational school students. This study employed a qualitative approach through an internship experience study. Data were collected through observations, interviews with principals, supervising teachers, industry representatives, students, and documentation. The findings reveal that students learned to adapt to the rhythm of industrial work, faced challenges due to differences in facilities and vehicle types, received direct guidance from industry mentors, and demonstrated behavioral changes toward greater discipline, responsibility, and communicative ability. Supervising teachers emphasized trustworthiness, honesty, discipline, and maintaining the school’s reputation, while internship experiences transformed students’ understanding of the relationship between religion, work, and their professional future. These findings indicate that internships are not merely job placements but also social processes that shape work habitus through direct industrial experience integrated with religious ethical values.